Technological Pedagogical Content Knowledge (TPACK) Guru pada Pembelajaran Matematika Siswa Sekolah Menengah Atas - Aridanthy, Vanya; Al Jupri, Al Jupri (Jurnal Studi Guru dan Pembelajaran, 2024)
The rapid development of technology and science in the 21st century requires individuals to adapt to emerging challenges. As a result, individuals must have 21st century skills to be able to deal with various problems and difficulties that arise. However, in Indonesia, the application of mathematics learning approaches and models is still largely dominated by a scientific approach combined with direct teaching, even though the government through the Ministry of Education has instructed to implement learning models that are constructive, interesting and innovative, such as discovery learning, problem-based learning, and project-based learning. To implement interesting and innovative learning in trigonometry material, knowledge of technology, pedagogy and content (TPACK) is one of the important factors that teachers must master. The purpose of this article is to report the use of a technology-based learning approach to develop mathematics teachers' TPACK competencies and the transformation of their knowledge in integrating technology into mathematics teaching practices. The research method used is descriptive qualitative to explain the concepts of TPACK analysis in learning. The results of this study illustrate that TPACK competencies can be specifically considered a core attribute for future mathematics teachers, because learning models using technological tools can help students develop mathematical understanding and influence the practice of mathematics teaching methods for teachers. In addition, mathematics teachers' TPACK competencies can have a direct impact on student learning in mathematics lessons. This shows that a technology-based learning approach can play an effective role in preparing and improving TPACK competencies for mathematics teachers.